Lightweight Threshing Rack under Multisource Excitation Based on Modal Optimization Method - Haotian Zhang; Zhong Tang; Yu Li; Xin Liu; Hui Ren (Advances in Materials Science and Engineering)
Crawler rice combine harvester threshing rack excited by different frequencies of multiple working parts would cause strong vibration response. In this paper, the rack-type rice combine harvester threshing rack was taken as research objective, and then the static analysis of the existing threshing rack was carried out by ANSYS Finite Element software. The topology of the rack structure was optimized according to the stress and strain distribution of the threshing rack. Based on solving the 6 natural frequencies and mode shapes of the threshing rack of combine harvester, the morphological test of threshing rack was carried out and the reliability of the modal analysis was verified. Finally, the multivibration source was assembled on the rack for simulation to test and verify the optimization effectiveness. Results showed that the 1st to 6th natural frequency of threshing rack after modal optimization could avoid the excitation frequency of the working part. Compared with the original design, the optimized threshing rack had a weight reduction of 13.7%. This study can provide a theoretical reference for the structural design and optimization of combine harvester threshing rack.